Scar among Bacillus Calmette-Guérin Vaccinated Children Presenting to an Immunisation Clinic at a Tertiary Hospital in Nepal: An Observational Study - Ajaya Kumar Dhakal; Divya KC; Barsha Shrestha; Devendra Shrestha; Nischal Neupane; Sharda Acharya; Saurav Shrestha (Journal of Nepal Medical Association)
Introduction: Bacillus Calmette-Guérin vaccination is associated with the development of scarring at the vaccination site in most children within 12 weeks of vaccination. However, due to various factors, some children do not develop scars. The aim of the study was to determine the prevalence of scar failure and the differences in clinical characteristics between scar-positive and scar-negative children. Methods: This observational cross-section study was conducted between 12 September 2022 and 15 April 2024 on children attending a vaccination clinic at a tertiary care hospital for 12 or 15-month vaccination. A purposive sampling method was used, and 386 children were enrolled in the study. During medical history, information was collected on Bacillus Clamettte-Guérin vaccination, child and maternal clinical profiles, and hospitalisations for respiratory tract infections in children. Results: Among 386 infants, prevalence of BCG scar was 341 (88.34%; 95% CI: 91.81%-91.37%). Vaccination was confirmed in 94.82% by history and card. The median scar size was 4mm (IQR: 2,5 mm) transversely and 3 mm (IQR: 2,5) vertically. Thirty-two (8.30%) infants required hospital admission for respiratory infections; none received anti-tubercular treatment. Conclusions: The BCG scar formation was higher compare to the scar failure. The scar failure was comparable to other studies.